Health-related quality of life among people living with type 2 diabetes: a community based cross-sectional study in rural Nepal - Sailendra Thapa; Prajjwal Pyakurel; Dharani Dhar Baral; Nilambar Jha (BMC, 2019)
Abstract Background Diabetes as being a chronic disease with a number of complications deteriorates the quality of life among the people with type 2 diabetes. Health related quality of life is widely used as an important health outcome measure worldwide. This study assessed the quality of life among the people living with type 2 diabetes in rural area of eastern Nepal. Methods A cross sectional study was conducted among type 2 diabetic patient of rural area of eastern Nepal. Pre-tested Nepali version of D-39 questionnaire was administered through face to face interview to assess the quality of life. Door to door visit was done to identify all the type 2 diabetic patients residing in Baniyani village. Data was entered in Micro-soft excel 2007 and further processed in SPSS v.11.5 for analysis. Results Highest quality of life mean (SD) score was in social burden domain (56.26 ± 12.07), followed by sexual functioning domain (54.35 ± 9.47), Anxiety and worry domain (54.33 ± 7.76), energy and mobility domain (51.46 ± 8.73) and diabetes control domain (50.08 ± 10.84). There was negative correlation between age and domains sexual functioning (p = 0.001) and energy and mobility (p = 0.002). In bivariate analysis, there was significance difference by sex in sexual functioning (p = 0.002), educational status in diabetes control (p = 0.021), smoking habit in energy and mobility (p = 0.038), duration of disease in diabetes control (p = 0.002) and sexual functioning (p = 0.001), presence of co-morbidity in social burden (p = 0.034) and family history of diabetes in anxiety and worry (p = 0.042). Conclusion Increasing age affects sexual life and mobility of the type 2 diabetic patient. The domain sexual functioning is difference by sex and presence of co-morbidity. Similarly, domain diabetic control is affected by duration of disease and educational status of the patient. And having family history of diabetes affects the mental state of the type 2 diabetic patient.